Combined Untargeted and Targeted Metabolomics Approaches Reveal Urinary Changes of Amino Acids and Energy Metabolism in Canine Babesiosis With Different Levels of Kidney Function - Kuleš, Josipa; Rubić, Ivana; Beer Ljubić, Blanka; Bilić, Petra; Barić Rafaj, Renata; Brkljačić, Mirna; Burchmore, Richard; Eckersall, David; Mrljak, Vladimir (Frontiers in Microbiology, 2021)
Canine babesiosis is a tick-borne disease caused by the haemoprotozoan parasites of the genus Babesia. Acute kidney injury is one of the most prevalent complication of canine babesiosis, and early diagnosis of altered kidney function remains a challenge in veterinary medicine. The aim of this study was to assess urine metabolic profile from dogs with babesiosis and different degree of kidney function using untargeted and targeted MS-based metabolomics approaches. In the study 22 dogs naturally infected with Babesia canis and 12 healthy dogs were included. Untargeted metabolomics approach identified 601 features with differential abundance between healthy group and groups of dogs with babesiosis and different level of kidney function, with 27 of them identified as match to known standards; while targeted approach identified 17 metabolites with significantly different concentrations between groups. A pattern of significantly altered metabolites referring to inflammatory host response, oxidative stress and energy metabolism modulation in babesiosis was presented. Our findings have demonstrated that kidney dysfunction accompanying the canine babesiosis was associated with changes in amino acid metabolism, energy metabolism, fatty acid metabolism, and biochemical pathways such as urea cycle and ammonia detoxication. These findings will be useful for further inclusion of urinary markers in clinical veterinary practice for the detection and monitoring of renal damage in babesiosis, as well as in other similar diseases.